Comparative study on physico-chemical of freeze and Hot-air dried goat leg extract. - SRUTHI D; SASIKALA SHANMUGAM (International Journal of Pharma and Bio Sciences, 2017)
Dietary habits are major factor in development of obesity and cardiovascular heart diseases. Foods from animal source have been a part of human diets for years. Goat meat also contains higher levels of iron, potassium, thiamine, and lower levels of sodium than beef. Considering its high nutritional value and its greater unsaturated to saturated fatty acid ratio, goat meat has the potential to improve health A systematic study to evaluate on how two drying methods namely hot air drying and freeze drying effects the goat leg meat water extract while conversion of the extract to powder form. Comparative studies were done on physicochemical and functional properties of the hot air and frieze dried powder which is critical for the utilization of the powder as an ingredient in food products. The water absorption capacity of the freeze-dried powder was higher than that of hot air dried. Similarly, solubility and rehydration ratio was comparatively higher for freeze dried powder. Results suggested that the freeze-dried powder could be a better for incorporating as food ingredient than the hot- air dried powder. Drying effects on its Total Phenolic Content [TPC] and Scavenging Activity [SA] was assayed which revealed that the freeze-dried sample showed a higher TPC than tray dried sample. Similarly freeze dried sample possessed better antioxidant activity than tray dried sample. On comparison with fresh sample small amount of changes were observed on both phenolic content and scavenging activity.